Households Behaviour on Solid Waste Management in English Bazar Municipality, Malda, India: An Insight from Primary Household Survey - Saha, Sampa; Roy, Ranjan (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Household behaviour is necessary to understand to develop effective solid waste management systems, particularly for rapidly developing urban municipalities such as English Bazar Municipality. The aims of the study are to identify the status of household behaviour on solid waste management. This study is based on a primary survey collected through schedules of total 2044 samples. In the study, the purposive random sampling technique is used. It is a cross-sectional study. The household survey was conducted in all the wards in the English Bazar Municipality in 2022-23. Segregation efficiency, recycling rate, waste composting rate, and proper disposal rate are calculated for measuring household’s behaviours on solid waste management, which classified into two categories, i.e. pro-environmentalist behaviours and anti- environmentalist behaviours. The maximum proportion of households (5.80 percent) is found to be pro-environmentalist behaviour of solid waste management at ward 15, followed by ward 13 (5.73 percent), and ward 5 (5.39 percent). The highest proportion of households (68.38 percent) is found to be anti-environmentalist behaviour of solid waste management at ward 27, followed by ward 29 (67.67 percent), and ward 24 (67.33 percent). The lowest proportion of households (59.32 per cent) is found to be pro-environmentalist behaviour of solid waste management at ward 2, followed by ward 3 (59.61 percent) and ward 13 (59.63 percent) in the study area. After analysis of households behaviours on the solid waste management in English Bazar Municipality, it is clear that the households behaviours depends on the waste generation, segregation, recycling, composting, and disposal of solid waste. Different dimension of the behaviour also depends on the socio-economic and demographic factors.